Dynamics of Tax Avoidance for the Construction Companies in Indonesia: A Study Financial Factor - Ekawarti, Yuni; Widyastuti, Sari Mustika; Alfiana, Yeni; Summagat, Lia (Yayasan Ilomata, 2025)
This study examines tax avoidance in Indonesia’s construction sector, focusing on the influence of profitability, capital intensity, and sales growth. Using data from 15 publicly traded construction firms on the Indonesia Stock Exchange (2020–2022), multiple linear regression analysis was applied to assess the relationship between these financial factors and tax avoidance, measured by the Effective Tax Rate (ETR). The research utilizes quantitative techniques to examine information from 15 construction firms that are publicly traded on the Indonesia Stock Exchange during the period of 2020-2022. Multiple linear regression analysis was used to analyze the data and examine the correlation between profitability, capital intensity, sales growth, and tax avoidance represented by the effective tax rate(ETR). These findings highlight the need for stricter monitoring of asset-intensive firms, as they tend to exploit tax-saving opportunities. Policymakers should evaluate depreciation-related tax benefits to ensure fair tax contributions and introduce enhanced disclosure requirements for high-growth firms. Strengthening regulatory oversight can prevent aggressive tax planning and promote equitable tax compliance. Future research could explore the role of corporate governance and industry-specific tax incentives in shaping tax behavior. Expanding the analysis to other sectors and regions would provide a broader understanding of corporate tax strategies. Ultimately, this study underscores the importance of balancing tax efficiency with regulatory compliance to ensure fiscal sustainability and a fair tax system